One-Step Preparation of Form-Stable Phase Change Material through Self-Assembly of Fatty Acid and Graphene - Akhiani A.R.; Mehrali M.; Tahan Latibari S.; Mehrali M.; Mahlia T.M.I.; Sadeghinezhad E.; Metselaar H.S.C. (American Chemical Society, 2023)
Fatty acids; Graphene; Heat transfer; Nucleation; Phase change materials; Saturated fatty acids; Self assembly; Enhanced heat transfer; Enhanced thermal conductivity; Form stable phase change material; Heterogeneous nucleation; Phase change enthalpy; Reduced graphene oxides; Supporting material; Three-dimensional structure; Palmitic acid